International students’ perspectives of Malaysian English teachers’ spoken English - Teh, June Li; Pilus, Zahariah (Indonesian Journal of Applied Linguistics, 2019)
Numerous studies comparing native and non-native English teachers have found that ESL students prefer native teachers for teaching speaking skills and pronunciation.  In other words, non-native teachers are viewed as less superior in matters related to spoken language.  This study explores international students’ views on spoken English of Malaysian teachers in English language classrooms. 81 international students who were attending English language classes as a preparation for university programmes at a Malaysian university participated in the study. The students were given a short writing task which required them to rate as well as stated their views on their Malaysian teachers’ spoken English in terms of speech rate, pronunciation, vocabulary, syntax, intelligibility, nativeness and acceptability for global communication. The study found that the international students considered the variety of Malaysian English used in the classroom as highly intelligible with high ratings for speech rates, vocabulary and sentence structures.  Malaysian English is also viewed as highly acceptable for global communication.  Although the teachers’ spoken language was rated lower for pronunciation and nativenesscompared to other traits confirming the views that non-native teachers are perceived as less proficient in pronunciation compared to the other skills, the ratings were still high indicating that in general, the acrolectal variety of Malaysian English as spoken in English classes is reasonably well accepted by other non-native speakers.